THE ROLE OF LEARNING GUIDANCE IN ESTABLISHING THE ATTITUDE OF INDEPENDENCE OF STUDENTS IN ELEMENTARY SCHOOL 247 PELITA - Jenal Abidin (Universitas Maritim AMNI Semarang, 2023)
The goal of this study is to discover the tutoring provided by the teacher to Elementary School 247 Pelita students, as well as the role of tutoring in the establishment of Elementary School 247 Pelita students' attitudes towards independence. In order to achieve these goals, the aforementioned research used a qualitative research approach with a special kind of study, with the instruments used being interviews, observation, and documentation. In addition, data analysis techniques such as data collecting, data reduction, data display, and generating conclusions are used. The findings revealed that tutoring routines were carried out by teachers after school through efforts such as providing effective learning methods, determining student study groups, holding meetings with students' parents, conducting remedial teaching, conducting enrichment teaching, increasing motivation for student learning, improving student skills, and improving student attitudes and good habits. Providing study advice to students who are slow and quick learners, such that students' attitudes towards improving independence, as seen by their initiative, responsibility, confidence, and self-control.